2005
DOI: 10.1177/073724770503100105
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Using Testing Accommodations: Student, Teacher, and Parent Perceptions of and Reactions to Testing Accommodations

Abstract: UniversityThis study examined student, parent, and teacher perceptions of the use of testing accommodations and the relationship between student perceptions of testing accommodations and their disability status and grade level. Students with and without disabilities completed math and reading achievement tests with and without accommodations. Students, parents, and teachers completed a questionnaire to share their views on the use of testing accommodations. Significant differences were found in the proportions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…S. N. Elliott and Marquart (2004) and Lang et al (2005) generally found the same effects of accommodations on motivation and comfort in students without disabilities. Lovett (2007) also found evidence for a unique, direct influence of test anxiety.…”
Section: Examinees’ Ability To Adapt To Standard Conditionsmentioning
confidence: 63%
See 1 more Smart Citation
“…S. N. Elliott and Marquart (2004) and Lang et al (2005) generally found the same effects of accommodations on motivation and comfort in students without disabilities. Lovett (2007) also found evidence for a unique, direct influence of test anxiety.…”
Section: Examinees’ Ability To Adapt To Standard Conditionsmentioning
confidence: 63%
“…Of the students with disabilities, 78% reported feeling more relaxed and 52% reported feeling more motivated during the double time administration. In a similar study, Lang et al (2005) gave students with disabilities (152 fourth graders and 142 eighth graders) math and reading tests under standard and accommodated conditions (here, the accommodations included extended time and other accommodations) and found that 46% of the students felt more comfortable when they took the tests with accommodations, whereas fewer than 10% felt more comfortable without the accommodations; and 62% of the students found the tests easier with accommodations, whereas fewer than 10% felt the opposite to be the case.…”
Section: Examinees’ Ability To Adapt To Standard Conditionsmentioning
confidence: 77%
“…Although most teachers agreed that response-mode accommodations for students with sensory impairments did not change the tested construct, they perceived accommodations that changed the test format and administration (such as extended time, reducing the number of items per page, and rewording questions) as changing the tested construct. In a similar study with 35 teachers and 43 parents, Lang et al (2005) found that most participants viewed accommodated tests taken by students with disabilities as only somewhat comparable to results from non-accommodated tests taken by students without disabilities. In the event that teachers' and parents' prior perceptions of the appropriateness of accommodations influence their willingness to recommend accommodations, bias may be introduced in the accommodation assignment process.…”
Section: Steps 3-4: Test and Item Specifications For The Saatmentioning
confidence: 91%
“…Student perception of test accommodations may also impact their willingness to request accommodations during IEP meetings. In a study with students in grades 4 and 8, Lang et al (2005) found that 62% of students with disabilities and 50% of students without disabilities classified the accommodated test as easier than the nonaccommodated test. Similarly, in a later study, Lang, Elliott, Bolt, and Kratochwill (2008) found that just under half of the students with and without disabilities preferred the accommodated condition.…”
Section: Steps 3-4: Test and Item Specifications For The Saatmentioning
confidence: 99%
“…Even though Lang, Kumke, Cowell, and Ray (2003) reported that while a significant majority of students with and without disabilities preferred taking accommodated tests, &dquo;some students disliked the accommodations because they felt they were unnecessary and slowed down the testing process&dquo; (p. 12) and &dquo;some students [even] resist or refuse accommodations&dquo; (Gibson et al, 2003, p. 4). Citing another unintended consequence of accommodations, Kettler, Niebling, Mroch, Feldman, and Newell (2003) found that 20% of the students with disabilities got lower scores on accommodated tests.…”
Section: Defining Accommodations and Modificationsmentioning
confidence: 95%